The Effect of Institutional Ownership, Independent Board of Commissioners and Profitability on Tax Avoidance in Technology Companies Listed on the Indonesia Stock Exchange - Sepika, Selly; Taufik, Kemal; Nurmansyah, Nurmansyah (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the effect of institutional ownership, independent board of commissioners, and profitability on tax avoidance in technology companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The research method used is quantitative with secondary data analysis from financial reports published through the Indonesia Stock Exchange website. Analysis techniques include descriptive statistics and multiple linear regression. The results of the study partially show that Institutional Ownership has a significant but negative effect on tax avoidance with a t-value of -6.350 and a significance of 0.028, which is greater than 0.05. The Independent Board of Commissioners has a significant but negative effect on tax avoidance, reflected in the t-value of -5.395 and a significance of 0.034, which is greater than 0.05. Likewise, profitability has a significant but negative effect on tax avoidance with a t-value of -1.758 and a significance of 0.048 greater than 0.05. Simultaneous analysis shows that the combination of these three variables as a whole has a significant effect on tax avoidance. In conclusion, each variable partially and simultaneously shows a significant influence on tax avoidance, which indicates that these factors need to be considered in the company's strategy related to tax avoidance. Keywords: Independent Board of Commissioners, Institutional Ownership, Profitability, Technology Companies, Tax Avoidance